Contributions of Faik Konica in Enriching Vocabulary of Albanian Through Word Formation - Luniku, Rakela (Richtmann Publishing, 2012)
Faik Konica had a genuine philological formation, and it seems in the way how we rigorously respected the law of linguistics.As a connoisseur of many excellent western language who has become an admirable job with the Albanian vocabulary, choosing it asone of the main ways to enrich the continuous vocabulary of the lexicon and its clearance from foreign word,word formation. His wordcreations are constructed so concise from the linguistic side, and sounds so beautiful in Albanian, that it regrets that has not survived thetime. It is enough to mention from his wonderful creations some of them in the local function, which: for the word chair he proposed